Japanese machizukuri and community engagement - Satoh, Shigeru (New York : Routledge, 2020)
"Over the past few decades, Japan has faced severe earthquake disasters, an increasing ageing population, declining birth rates and widening social disparities. These issues have served to highlight gaps left by top-down governance approaches and the urgent need to create resilient societies using more traditional models"--
OCLC-licensed vendor bibliographic record.
Keywords: Community development -- Japan; City planning -- Japan -- Citizen participation; Urban policy -- Japan -- Citizen participation; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning